Cartas de Luis Castro López a Roberto H. Todd - Todd, Roberto H.; Castro López, Luis (My University, 1903)
Cartas relacionadas a felicitaciones por el nombramiento de Todd para alcalde.
Keywords: Castro López, Luis--Correspondencia.; Castro López, Luis--Correspondence.; Todd, Roberto H.--Correspondencia.; Todd, Roberto H.--Correspondence.